THE AUTOMOTIVE SECTOR IN SPAIN. INFLUENCE OF R&D INVESTMENT ON THE IMPROVEMENT OF TOTAL FACTOR PRODUCTIVITY - Miró-Pérez, Albert-P.; Crisóstomo Gálvez, Raquel; Carreño, Marc Valderrama (Management and Administration Journal, 2020)
The current globalised environment has been preceded by a generalised increase in the diffusion and use of Information and Communication Technologies (ICT), as well as by a large investment in Research and Development (R&D) by companies. This circumstance makes the use of these technologies fundamental for the automotive sector to face with guarantees the growing international competitivity. Thus, the correct use of ICT provides an improvement in productivity, and therefore in the competitiveness of enterprises. This article analyses the evolution of total factor productivity (TFP) in the Spanish automotive sector for the year 2017, in order to determine the influence this variable has on the improvement of total factor productivi